The Excerpta Latina Barbari and the 'Picus-Zeus narrative - Garstad, Benjamin (My University, 2002)
The gods of the Greeks and Romans, we know did not pass away with the neglect of their cults, the crumbling of their temples, and the denigration of their myths. They lived on in Byzantium and the Latin West, but sometimes their disguises, the strange permutations to which their characters, attributes, and stories were subjected, rendered them almost unrecognizable. One of these peculiar forms of survival was what we shall henceforth refer to as the 'Picus-Zeus narrative', The Picus-Zeus narrative, briefly summarized, relates that Cronus was an Assyrian king who left the East to found a kingdom in Italy, and that he was followed in this by his son Picus, also called Zeus; Picus-Zeus, it continues, had a son, Hermes (also called Faunus), who left Italy and established himself in Egypt. The narrative involves many other characters from the Greek pantheon and from as the Greeks knew it, but this should be a sufficient summary of its basic plot. This may seem, at first, to be nothing more than an obscure and bizarre example of mythological rationalization, but in the Byzantine chronicle tradition it was for hundreds of years the principal explanation of the role of so-called gods in the properly historical events of the world, and versions of it are found in works form such diverse regions as Bulgaria and Ethiopia,
Keywords: Greek and Roman gods; Byzantium; Latin West; Picus-Zeus narrative; Cronus; Hermes; Italy; Egyp; Assyrian history; mythological rationalization